MICROFINANCE AND MOBILE MONEY: DIFFERENT REGIONS AND INCOME LEVEL - Borjana Stojkova, Klimentina Poposka, Iskra Stanceva Gigov (Institute of Economics-Skopje, University “Ss. Cyril and Methodius” in Skopje, Republic of North Macedonia, 2021)
Microfinance and mobile money have recently become very popular globally. There is hardly a country in the world that is not using the benefits of microfinance and mobile banking. Digitization increasingly intensify their use. However, the different degree of development of economies and digitalization level determinate the use of these categories in the various regions and in the countries with different income levels. Hence, the purpose of this paper is to explore whether there are statistically significant differences in the level of microfinance and mobile money between regions, but also between grouped countries based on different income levels. The research is based on the various available data and indicators regarding microfinance and mobile money that are used as observation in the one-way ANOVA analysis. The analysis indicates significant differences in the level of microfinance and mobile money according to the income levels of the countries. Namely, the countries with higher level of income have higher level of microfinance and mobile money. Also, no evidence was found of differences in microfinance levels between the regions proposed for testing as groups.
Keywords: microfinance, mobile money, microfinance institutions, regions, income level